Local Culture Preservation through Southern Thai-based English Lessons - Budsaba, Kanoksilapatham (Pusat Pengajian Ilmu Kemanusiaan, 2019)
The current established status of English as a global language has been triggered by the trend of globalization. Consequently, the majority of people around the world are enticed by this status because it means that communication across the globe is facilitated through the use of the English language. However, some people, in contrast, are feeling troubled or distressed by fear that their own native language is decreasing in popularity. In addition, a number of traits or characteristics associated with national identities which have been shaped by national history and passed down for generations are jeopardized. These concerns regarding the increasing influx of influence generated by, or related to, the English language through a multitude of channels have been exacerbated by the augmented popularity of social media that permeates most aspects of people’s lives.